1995
DOI: 10.1161/01.cir.91.5.1512
|View full text |Cite
|
Sign up to set email alerts
|

Catecholaminergic Polymorphic Ventricular Tachycardia in Children

Abstract: The entity of adrenergic-dependent, potentially lethal tachyarrhythmia with no structural heart disease deserves to be individualized. It may form a variant of the congenital long QT syndrome in which the ECG marker is lacking; this primary ventricular arrhythmia must be looked for in a pediatric patient with stress- or emotion-induced syncope because only beta-blocking therapy can prevent sudden death and therefore must be given for the patient's lifetime.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
708
2
16

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 903 publications
(738 citation statements)
references
References 31 publications
12
708
2
16
Order By: Relevance
“…SD was evoked by three different methods: For K-SD, a 1 M KCl microejection pipette was placed at the slice surface. The KCl microinjection was started with a 10-ms pulse (constant 40 psi), and the ejection duration was incrementally escalated up to 500 ms (10,20,50, 100, 300, and 500 ms) every 3 min. OGD-SD was induced by exposure to ACSF with reduced glucose (2 mM glucose/8 mM sucrose or 5 mM glucose/5 mM sucrose) and saturated by nitrogen (95% N 2 /5% CO 2 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SD was evoked by three different methods: For K-SD, a 1 M KCl microejection pipette was placed at the slice surface. The KCl microinjection was started with a 10-ms pulse (constant 40 psi), and the ejection duration was incrementally escalated up to 500 ms (10,20,50, 100, 300, and 500 ms) every 3 min. OGD-SD was induced by exposure to ACSF with reduced glucose (2 mM glucose/8 mM sucrose or 5 mM glucose/5 mM sucrose) and saturated by nitrogen (95% N 2 /5% CO 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Most cases of sudden cardiac death in CPVT are considered to be due to ventricular tachycardia/fibrillation driven by sympathetic stimulation (47). Paradoxically, many patients show sinus bradycardia at rest (22,(48)(49)(50), and not a small fraction of death is related to AV block and bradycardia (51). The RQ mouse showed this bradycardia phenotype (Fig.…”
Section: Rq Mutation Selectively Enhances Excitatory Synaptic Transmimentioning
confidence: 99%
“…10,11 Mortality rates are high, reaching 30% to 50% in patients aged Յ30 years. 12 The original definition of CPVT described children with stress-induced ventricular arrhythmias that are predominantly bidirectional ventricular tachycardias, 10 whereas the FPVT patients have predominantly polymorphic ventricular tachycardia.…”
mentioning
confidence: 99%
“…10,11 Mortality rates are high, reaching 30% to 50% in patients aged Յ30 years. 12 The original definition of CPVT described children with stress-induced ventricular arrhythmias that are predominantly bidirectional ventricular tachycardias, 10 whereas the FPVT patients have predominantly polymorphic ventricular tachycardia. 8 Priori et al 7 reported 4 RyR2 missense mutations, 3 of which (S2246L, R2474S, and N4104K) were sporadic and one (R4497C) of which was found in a family with 5 clinically affected mutation carriers.…”
mentioning
confidence: 99%
“…95 Familial history of syncope or sudden death exists in 30% of patients. 95 The gene encoding the ryanodine receptor regulates intracellular calcium flux and is affected in autosomal dominant CPVT. 96,97 Evaluation for premature CAD, cardiac catheterization for anomalous coronary arteries, and echocardiogram or MRI for ARVD and other etiologies should be considered in patients with exercise precipitated syncope.…”
Section: Catecholminergic Polymorphic Ventricular Tachycardia (Cpvt)mentioning
confidence: 99%